STRATEGI PENGEMBANGAN KOPERASI AGRO SIGER MANDIRI DI KECAMATAN KALIANDA KABUPATEN LAMPUNG SELATAN - Ellis Nurhidayati; Dyah Aring Hepiana Lestari; Adia Nugraha (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2015)
The objectives of this research were to: determine the operation performance of Agro Siger Mandiri cooperation; determine the contribution of Agro Siger Mandiri cooperation to regional development; and determine the welfare level of members of Agro Siger Mandiri cooperation according to the criteria of BPS in 2007; in addition to formulate appropriate development strategies as development efforts in the Agro Siger Mandiri Cooperation.  This research was conducted by case study method.  This study employed qualitative descriptive analyses and quantitative analysis method.  The results showed that the performance assessment of Agro Siger Mandiri cooperation showed less quality; this cooperation did not have any contributions to regional development; and all members of Agro Siger Mandiri cooperation were in welfare category.  The priority strategies that could be used in the development and sustainability of Agro Siger Mandiri cooperation were creating and managing a clear transaction records to determine the financial condition and data of cooperation, utilizing technology to improve product quality and enhance its marketing networks, as well as conducting trainings to improve skills of cooperation administrators and members of cooperation to be able to innovate. Key words: contribution, performance, SWOT, welfare